Рассказы о Гагарине - Нагибин Юрий Маркович (Детская литература, 2011)
Экземпляры: (20110519) / Инвентарный номер: 46974 / Цена: 228.47 / Сис.шифр: 84(2Рос=Рус)6 46974 / Авт.знак: Н 16 / ББК: 84(2Рос=Рус)6